Developing a PISA-Like Mathematical Problem: Using Traditional Food Context - Gustiningsi, Tria; Putri, Ratu Ilma Indra; Zulkardi, Zulkardi; Hapizah, Hapizah (IJECA (International Journal of Education and Curriculum Application), 2023)
Mathematical literacy is very important for all students. Based on the PISA results, Indonesian students' mathematical literacy skills are still low, so students need to be trained with PISA-like mathematical problem. This study aimed to produce a valid and practical PISA-like mathematical problem using the context of Palembang traditional food. Design research in the form of a development study was chosen in this study which consisted of preliminary and prototyping stages. Data collection was carried out using walk-throughs, tests, questionnaires surveys, and interviews. The research subjects were 20 eighth graders. Materials on relations and functions were delivered in this study using a personal context through the activity of purchasing Palembang traditional food. Data were analyzed descriptively. The results of this study indicated that the problem developed is valid and practical. The problem was considered valid as it was developed in accordance with the PISA framework, as well as the curriculum and materials for the eighth grade. The problem was also declared practical, meaning that it is viabel to use for students, its wording does not cause multiple interpretations, it is understandable to students, the tables and numbers used are clear, and students are interested in solving it because it is relevant to everyday life situations. The problem developed also has a potential effect on supporting students' mathematical literacy skills. This study concludes that problem that has been developed is valid, practical, and has potential effect.